A phase I study of lenalidomide plus chemotherapy with mitoxantrone, etoposide, and cytarabine for the reinduction of patients with acute myeloid leukemia. Issue 2 (21st November 2017) - DeAngelo, Daniel J.; Brunner, Andrew M.; Werner, Lillian; Avigan, David; Fathi, Amir T.; Sperling, Adam S.; Washington, Abigail; Stroopinsky, Dina; Rosenblatt, Jacalyn; McMasters, Malgorzata; Luptakova, Katarina; Wadleigh, Martha; et al.
Abstract: Patients with relapsed AML have a poor prognosis and limited responses to standard chemotherapy. Lenalidomide is an immunomodulatory drug that may modulate anti‐tumor immunity. We performed a study to evaluate the safety and tolerability of lenalidomide with mitoxantrone, etoposide and cytarabine (MEC) in relapsed/refractory AML. Adult patients with relapsed/refractory AML were eligible for this phase I dose‐escalation study. We enrolled 35 patients using a "3 + 3" design, with a 10 patient expansion cohort at the maximum tolerated dose (MTD). Lenalidomide was initially given days 1‐14 and MEC days 4‐8; due to delayed count recovery, the protocol was amended to administer lenalidomide days 1‐10. The dose of lenalidomide was then escalated starting at 5 mg/d (5‐10‐25‐50). The primary objective was tolerability and MTD determination, with secondary outcomes including overall survival (OS). The MTD of lenalidomide combined with MEC was 50 mg/d days 1‐10. Among the 35 enrolled patients, 12 achieved complete remission (CR) (34%, 90%CI 21‐50%); 30‐day mortality was 6% and 60‐day mortality 13%. The median OS for all patients was 11.5 months. Among 17 patients treated at the MTD, 7 attained CR (41%); the median OS was not reached while 12‐month OS was 61%. Following therapy with MEC and lenalidomide, patient CD4+ and CD8+ T‐cells demonstrated increased inflammatory responses to autologous tumor lysate. The combination of MEC and lenalidomide is tolerable with an RP2D of lenalidomide 50 mg/d days 1‐10, yielding encouraging response rates. Further studies are planned to explore the potential immunomodulatory effect of lenalidomide and MEC.